Proceedings of Symposium on the Earth's Gravitational Field and Secular Variations in Position - Symposium on the Earth's Grativitional Field and Secular Variations in Position (1973 : University of New South Wales, Sydney); Angus-Leppan, P.V.; University of New South Wales. School of Surveying (Sydney : School of Surveying, University of New South Wales, 1974)
26